The Association Between Level of Physical Activity and Body Mass Index, and Quality of Life Among Elderly Women - Ðošić, Anđela; Živković, Danijela; Milanović, Zoran; Živković, Mladen; Bjelaković, Ljiljana; Bratić, Marija; Pantelić, Saša (Frontiers in Psychology, 2021)
The process of ageing leads to changes in functional abilities, fitness levels, level of physical activity, and BMI, all of which causes changes in the quality of life. The current study aims to determine the association between the level of physical activity (PA) and BMI, and quality of life (QoL) among elderly women. The total sample numbered 156 women, with an average age of 67.7±5.6 yrs. To determine the level of physical activity, the self-reported International Physical Activity Questionnaire Long Form (IPAQ-LF), was used. To calculate the values of the BMI, the standard procedure recommended by the World Health Organization was used. Quality of life was evaluated using the short form of the WHOQOL-BREF questionnaire designed by the World Health Organization. All the data were processed using the statistical package for data analysis SPSS 20.0. Pearson’s correlation analysis shows statistically significant relations at the level of p<.01 between PA and Physical health in Housework = .36, Leisure time PA = .27, Walking = .24, Moderate PA .43, Total PA = .43, while the correlations between the variables at the significance level of p<.05 were determined in PA in transportation = .19 and High-intensity PA = .16. Multiple linear regression analysis of different levels of PA as independent variables on individual domains of QoL shows that there is an association of PA and Physical health (Sig= .000), more precisely, Total PA is statistically the most closely related to Physical health (Sig= .000), and then follows PA at work and Social relations (Sig= .036). Similar results were obtained when BMI is added to model A. In contrast to model A, model B shows a statistically significant association between PA and BMI with the environmental domain of QoL (Sig= .001). The results of the current study indicate that high- and moderate-intensity physical activity both have benefits for physical health, whereas moderate PA showed higher significance levels. Results also show that elderly women with higher BMI values achieve better results in the environmental domain of QoL.